Deployment planning tool for environmentally sensitive heavy-duty vehicles and fueling infrastructure. (December 2022) - Lane, Blake; Kinnon, Michael Mac; Shaffer, Brendan; Samuelsen, Scott
Abstract: A novel planning tool is introduced for projecting vehicle and fueling infrastructure deployment of near-zero and zero emission heavy-duty vehicles (HDVs). To address climate change and air quality goals, the tool is based on a systematic methodology to develop rollout scenarios that meet environmental goals at the lowest cost, and identify policy to facilitate the deployment. Called TRACE (Transportation Rollout Affecting Cost and Emissions), the methodology provides a framework for developing and analyzing scenarios that consider the technical and socio-political constraints and incentives in the emerging HDV sector. For the California Greenhouse Gas (GHG) Scenario requiring an 80% reduction in 1990 GHG levels by 2050, TRACE projects a significant population of biomass-sourced renewable diesel-fueled internal combustion vehicles, complemented by a substantial population of battery and fuel cell electric powertrain adoption by 2050. In contrast, the Zero Emission Vehicle Scenario projects a near-complete (100%) adoption of battery and fuel cell electric powertrains by 2050 with a 0.53% higher cumulative cost than the GHG Scenario. The policy implications include a need for (1) near-term benefits of low/negative carbon intensity biomass without diminishing adoption of zero emission HDVs, and (2) both renewable fuel and fuel cell electric vehicle incentives tailored to vocational demand. Highlights: A novel method of projecting fuel and vehicle cost and deployment is introduced. Strict zero emission vehicle mandates reduce 2050 emissions with little added cost. Limited biomass availability increases electrolytic fuel production importance. Policy is needed to support heavy-duty fuel cell vehicles and low carbon fuels. Mid-term emissions may benefit from support of low carbon natural gas vehicles.